If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 6p + 3 = 2p Reorder the terms: 1 + 3 + 6p = 2p Combine like terms: 1 + 3 = 4 4 + 6p = 2p Solving 4 + 6p = 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 4 + 6p + -2p = 2p + -2p Combine like terms: 6p + -2p = 4p 4 + 4p = 2p + -2p Combine like terms: 2p + -2p = 0 4 + 4p = 0 Add '-4' to each side of the equation. 4 + -4 + 4p = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 4p = 0 + -4 4p = 0 + -4 Combine like terms: 0 + -4 = -4 4p = -4 Divide each side by '4'. p = -1 Simplifying p = -1
| 14(t-2)+7t=7(3t+4)-8 | | =2+7-8 | | =412+1 | | 2xz+6yz+x+3y= | | d=2c+3c | | 3/7r=9 | | 2p+6+4=-4P | | sqrt(7+6x)+sqrt(4x+5)=2 | | 8(11+n)= | | 8n+11= | | 8+11n= | | 8(11)+n= | | x-5(3-x)=9 | | x(12x+7)-10=0 | | 1/5y-1/32/3 | | =35*700 | | 7.2+1.87=19.8 | | 96/-(x-74)=3 | | 0.7+5= | | 12(3x+3)-5(2x-6)=6x-54 | | log(x+4)(x-2)=1 | | -(5x-15)+4(6x+6)= | | 2y-6y+3y-7= | | ?x+3=8 | | 1/3*12x | | x^(-9/11) | | x^-9/11 | | x^2+2xy^2+y^2=0 | | t^2+12t-5=0 | | 8+5n-4=8n+10-2n | | 0.30x+0.15(180)=0.15(80) | | -8(x+5)-3=-43 |